PERAN LEMBAGA STUDI MAHASISWA ISLAM (LSMI) ALMADANI DALAM PEMBINAAN KARAKTER RELIGIUS DI FISIP UNIVERSITAS RIAU - Munawwarah "; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Institute of Islamic Students Study (LSMI) Almadani is a formal manifestation of the Islamic Da'wah movement conducted by students who feel concerned with the condition of existence of movement in the campus. Besides broadcasting Da'wah, Da'wah institutions also participated in forming a religious student manipulation, in the LSMI Almadani students have been in development from the beginning into the realm of lectures, LSMI Almadani always record new students each year, this is done solely to help new students and advise on the importance of studying religious sciences. Through this research researchers want to know the role of LSMI Almadani in the development of religious character of the University of Riau FISIP students and the role of inhibitory factor LSMI Almadani in the construction of religious characters FISIP University of Riau. This research is a qualitative descriptive study that makes individuals as the subject of research. The research informant is determined by the purposive procedure. Data collected using 3 methods: Interview, observation and documentation. In conducting the informant interview is the administrator of LSMI Almadani, a student of mentoring and FISIP students who have the criteria of informant in this research that amounted to 7 informant. Data interpretation is done gradually ranging from data collection, data reduction to the obtaining of conclusions and research recommendations. From the results of research that has been done LSMI Almadani is an Islamic organization that can be an alternative for FISIP students who want to process with activities made such as mentoring and study. And the factor that is becoming a inhibitor of LSMI Almadani in performing its role as a building container of religious character FISIP UNRI students are internal and external factors. Keywords: Role, LSMI Almadani, Character